2016
DOI: 10.1007/s10854-016-5168-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper concentration on the physical properties of ZnS:Cu alloys prepared by chemical bath deposition

Abstract: ZnS:Cu thin films were deposited on glass substrates by chemical bath deposition technique. The structural, morphological, optical and electrical properties of the grown films were characterized by X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectrometry, scanning electron microscopy, spectrophotometry, spectrofluorimetry and Hall effect measurements. Both XRD and Raman analysis indicated the coexistence of both sphalerite ZnS and covellite CuS with cubic and hexagonal structures, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…With Cu dopant, wurtzite phase contribution is seen to increase. [ 28 ] However, when Mg and Cu are used as dopants, possible good results are obtained if the host has a zinc blende structure. [ 29 ] In other words, at a higher dopant concentration, film growth could be non‐oriented, yielding poor crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…With Cu dopant, wurtzite phase contribution is seen to increase. [ 28 ] However, when Mg and Cu are used as dopants, possible good results are obtained if the host has a zinc blende structure. [ 29 ] In other words, at a higher dopant concentration, film growth could be non‐oriented, yielding poor crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…To improve their electrical and optical properties, researchers have explored various strategies, including optimizing the synthesis conditions and doping with impurities such as zinc or cadmium. For example [140], reported that zinc-doped CuS films exhibited a higher electrical conductivity and lower resistivity compared to undoped CuS films. Optimizing the annealing temperature and time can lead to significant improvements in the structural and optical properties of CuS films [120].…”
Section: Case Studies Of Successful Improvements In Electrical and Op...mentioning
confidence: 99%